The Good Name Of The Corporate Taxpayer In Moderating The Influence Of Technical Knowledge, Moral Obligations, Quality Of Service And Taxpayer Compliance - Agustinus, Agustinus (Journal of Social Research, 2023)
The purpose of this study is to determine the level of mandatory compliance of the entity in carrying out tax obligations when it already has technical knowledge, moral obligations and quality of service as well as whether the Good Name of Taxpayers can improve taxpayer compliance. The research method was carried out quantitatively and analyzed using SMARTPLS 3.0 software. The results showed that all independent variables had a positive effect on taxpayer compliance, then the good name of taxpayers could only moderate the quality of service to taxpayer compliance.